2008
DOI: 10.1007/s12094-008-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Neck dissection after radiochemotherapy in patients with locoregionally advanced head and neck cancer

Abstract: Patients with N2/N3 disease who obtained a clinical and radiological CR to chemoradiation had a zero incidence of isolated neck failure without a planned ND. The continued use of planned NDs in this patient subset may not be justified. This can be further confirmed in randomised prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In many malignant tumors, it is well known that successful treatment is correlated with an increase in ADC values (4950515253). Additionally, the ability of DWI to predict treatment outcome at one to three weeks after the start of treatment seems to be in agreement with the expected optimal timing of adjuvant neck dissection after CCRT or radiotherapy (545556).…”
Section: Discussionsupporting
confidence: 66%
“…In many malignant tumors, it is well known that successful treatment is correlated with an increase in ADC values (4950515253). Additionally, the ability of DWI to predict treatment outcome at one to three weeks after the start of treatment seems to be in agreement with the expected optimal timing of adjuvant neck dissection after CCRT or radiotherapy (545556).…”
Section: Discussionsupporting
confidence: 66%
“…Cooper et al [8] have also reported that postoperative radiotherapy and chemotherapy can improve disease-free survival and improve local and regional control rate in patients with head and neck squamous cell carcinoma. López Rodríguez et al [9] have reported that preoperative radiotherapy and chemotherapy for head and neck squamous cell carcinoma at N2-N3 stage can completely control neck lymph node metastasis and achieve local and regional effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A potential advantage of radiation compared to surgery in this setting is that potential primary sites in the head and neck may be included in the radiation field. Neck dissection following irradiation may be required for nodal residual disease (34). A nodal excision may be sufficient when radical, comprehensive irradiation to the neck and mucosal sites is planned (30).…”
Section: Treatmentmentioning
confidence: 99%